Hepatocellular Carcinoma-Associated Polymyositis Presenting With Unilateral Upper Limb Subcutaneous Edema - Tsai MENG-KO,; Chen YI-HSIN,; Chiu YOU-HSIN,; Lai KUO-LUNG, (Archives of Rheumatology, 2018)
Localized subcutaneous edema is a rare manifestation of inflammatory myopathy. In general, the incidence of malignancy in dermatomyositis is higher than that in polymyositis (PM). The association between malignancy and dermatomyositis has been established; however, it is less convincing in PM. In this article, we report on a case of malignancy-associated PM with an initial presentation of localized subcutaneous edema. A 66-year-old male patient with a history of chronic hepatitis B was presented to us with both left arm swelling and progressive proximal muscle weakness. A multi-detector row computed tomography showed prominent left arm edema, while a venography demonstrated no venous thrombosis or stenosis. A diagnosis of PM was established according to its typical symptoms, high serum creatine kinase level, positive electromyography findings, and systemic inflammatory signs. Magnetic resonance imaging of the liver revealed infiltrative hepatocellular carcinoma. After undergoing systemic corticosteroid therapy, in combination with hydroxychloroquine, the left arm edema was resolved. However, patient died from hepatocellular carcinoma three months after the date of diagnosis. It is important to recognize that hepatocellular carcinoma-associated PM may initially present itself with localized non-pitting edema. Although such localized edema may be responsive to corticosteroids, a patient’s overall prognosis remains poor. We presume that PM with localized subcutaneous edema may be a predictor of malignancy, and therefore recommend a tumor survey.